Top manager effects on buprenorphine adoption in outpatient substance abuse treatment programs. - Friedmann PD; Jiang L; Alexander JA; Friedmann, Peter D; Jiang, Lan; Alexander, Jeffrey A (Journal of Behavioral Health Services & Research, 2010)
To examine the influence of top managers' characteristics on the adoption of buprenorphine for opioid dependence among U.S. outpatient substance abuse treatment units, this investigation analyzed a cross-sectional national study of 547 such units in the 2004-2005 wave of the Drug Abuse Treatment System Survey. Administrators reported their demographics, training, and treatment orientation, as well as features of the unit and its pattern of use of buprenorphine. Nationally, 15.8% of programs offered any buprenorphine services. Greater adoption of buprenorphine correlated with directors' younger age, longer tenure, male gender, and weaker endorsement of abstinence as the most important treatment goal. Availability of naltrexone and medical services also correlated positively with buprenorphine adoption. The authors conclude that leaders' characteristics are related to the adoption of innovative practices in addiction treatment programs. Future work should examine whether leadership development for community addiction programs might speed up the diffusion of buprenorphine and other innovative, evidence-based practices.